ORGANOLEPTIK KEFIR SUSU KAMBING DENGAN WAKTU LAMA FERMENTASI - Sri Ali Wahyuni Ginting (Bajang Institute, 2024)
The research aims to determine the Organoleptic of Goat's Milk Kefir with different fermentation times. The research used a descriptive method using 3 treatments and 6 replications with a completely randomized design with a non-factorial pattern. With treatment P1 (24 hour fermentation), P2 (36 hour fermentation), P3 (48 hour fermentation). The research results showed that goat's milk kefir with different fermentation times had no significant effect on the organoleptic test of goat's milk kefir. kefir that was fermented for 36 hours was the kefir that the panelists liked with an aroma rating of 2.51 using the kefir aroma criteria, taste 2.90 with the criteria being slightly sour, color 2.44 with the criteria being white